Immune checkpoint inhibitor-related pneumonitis with atypical radiologic features in a patient with anti-aminoacyl-tRNA synthetase antibody - Seiya Ichihara; Hirokazu Ogino; Hiroto Yoneda; Keiko Haji; Kozo Kagawa; Kojin Murakami; Masato Mima; Yu Aoi; Atsushi Mitsuhashi; Yuki Tsukazaki; Yohei Yabuki; Ryohiko Ozaki; et al. (Respiratory Medicine Case Reports, 2023)
A man with non-small-cell lung cancer who was negative for anti-nuclear antibodies was admitted for dyspnea after immune checkpoint inhibitor (ICI) administration. Computed tomography (CT) showed complexed radiologic features, including subpleural and basal predominant reticular shadow with cystic structures and peribronchovascular consolidation. Although we treated him with high-dose steroid under a diagnosis of ICI-related pneumonitis, he developed acute exacerbation of pneumonitis with progressive fibrosis and volume loss. A re-evaluation identified anti-aminoacyl-tRNA synthetase antibody in the serum collected before ICI administration. This case highlights the importance of re-evaluating pre-existing autoimmune disorders in patients who develop ICI-related pneumonitis with atypical radiologic features.